2021
DOI: 10.3892/mmr.2021.11842
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of natural adenosine monophosphate‑activated protein kinase activators through virtual screening and activity verification studies

Abstract: The adenosine monophosphate-activated protein kinase (aMPK) is a promising target in drug development for various metabolic diseases. in the present study, the aim was to discover natural direct aMPK activators from natural sources, thus a virtual screening for direct aMPK activators was conducted by combining ligand-based and structure-based screening. a common-feature pharmacophore model (HipHop1) was generated with two hydrogen bond acceptor lipid features and one hydrophobic region feature. a total of 1,23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Due to the essential role of AMPK on glucose and lipid metabolism, the exploration of molecules that can activate AMPK is an emerging field both in pharmacology and nutrition (Grahame Hardie, 2016; Hao et al , 2021; Olivier et al , 2018). Several bioactive compound such as phenolic compound and polyphenols have been reported to activate AMPK and ameliorate glucose uptake in insulin resistance condition (Huang et al , 2015; Vazirian et al , 2018; Momtaz et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the essential role of AMPK on glucose and lipid metabolism, the exploration of molecules that can activate AMPK is an emerging field both in pharmacology and nutrition (Grahame Hardie, 2016; Hao et al , 2021; Olivier et al , 2018). Several bioactive compound such as phenolic compound and polyphenols have been reported to activate AMPK and ameliorate glucose uptake in insulin resistance condition (Huang et al , 2015; Vazirian et al , 2018; Momtaz et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature (PubMed search with terms "AMPK" and "QSAR"), several QSAR models for prediction of AMPK activation have been published so far [24][25][26][27][28][29][30]. However, all of these models used pharmacophore docking analyses or homology models or structure-, ligand-, or fragment-based design and focused exclusively on direct AMPK activators.…”
Section: Discussionmentioning
confidence: 99%
“…47 Similarly, a previous study proposed that AMPK activators should possess a favorable feature, which is the formation of a salt bridge with Lys29. 48 Furthermore, a former in vitro study has shown the potential of beta-sitosterol as an AMPK activator, by increasing the expression of AMPK in L6 myotube cells. 49 Thienopyridone (synonym A-769662) and metformin were used as standards because these two drugs are well-known as AMPK activators.…”
mentioning
confidence: 99%